Examining the dominant, emerging, and waning themes featured in select HRD publications: Is it time to redefine HRD?. Issue 4 (29th April 2014) - Ghosh, Rajashi; Kim, Minjung; Kim, Sehoon; L. Callahan, Jamie
Abstract : Purpose: – The purpose of this study is to identify how themes and contributions featured in the four scholarly journals sponsored by the largest human resource development (HRD) research association (the Academy of Human Resource Development, AHRD) reflect the changing identity of the HRD field. Design/methodology/approach: – A frequency and content analysis of articles published during the period 2002-2011 was conducted to identify the dominant themes and research trend. Further, comments were made on the aims and scope and editorial discretion for each journal to understand how the journals influence the direction of scholarship in HRD. Findings: – It was found that the boundaries of the field are constantly expanding with some of the older and mature themes losing momentum and new themes coming to the forefront of scholarly interest. The journals were found to play a critical role in setting the future direction for the field. Research limitations/implications: – Future researchers can examine if the waxing and waning themes identified in the findings remain same after analyzing contributions featured in journals that are not sponsored by the AHRD, but publish articles on topics closely related to HRD. Also, the findings can guide further examination of the editors' leadership role in driving the evolution of the HRD field. Practical implications: – Considering the characteristics of HRD as an applied discipline, the findings can guide future researchers to explore if the thematic changes as identified in the study are associated with the needs of HRD practice. Originality/value: – The study attempts to understand the landscape of HRD research by looking at how the field's identity boundaries have shifted over time and how different entities, like authors and editors publishing scholarly articles in the four HRD journals in the past decade, have interacted to contribute to the shift.